2011
DOI: 10.4236/snl.2011.11003
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Step Process for Preparing Supercapacitor Electrodes from Carbon Nanotubes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Ni-foam-based CNTs retained almost 72% of the initial capacitance at a high current density. 88 Compact-designed supercapacitors were fabricated using large-scale freestanding and flexible SWCNT films as electrode materials. 89 The SWCNT films were prepared by floating CVD method.…”
Section: Cnt-based Materialsmentioning
confidence: 99%
“…Ni-foam-based CNTs retained almost 72% of the initial capacitance at a high current density. 88 Compact-designed supercapacitors were fabricated using large-scale freestanding and flexible SWCNT films as electrode materials. 89 The SWCNT films were prepared by floating CVD method.…”
Section: Cnt-based Materialsmentioning
confidence: 99%
“…Pushparaj et al, 2007 [12], used as electrode MWNTs aligned perpendicularly to the current collector and embedded in cellulose, and they fabricated supercapacitors with a maximum power density of 1.5 kW/kg for an RTIL electrolyte. Shi et al [13] reported that growing carbon nanotubes directly on the nickel foam current collector lowered the internal resistance. Ma et al [14] reported the inclusion of MWNTs in phenolic resin mixtures and carbonisation of the mixture at 850…”
Section: Introductionmentioning
confidence: 99%
“…The CNTs could be fabricated through different methods. Shi et al [110] stated the importance of CNTs synthesize method on the performance of the electrode. CNTs were grown on 3D porous nickel (Ni) foam by means of the single-step CVD method, in which the resultant electrode exhibited a superior capacitive performance at higher current densities, less ESR, and a capacitance about 127% greater than the CNT electrode fabricated through the conventional transfer technique.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%